Morphological and Molecular Characterization of Toxigenic Aspergillus flavus from Groundnut Kernels in Kenya - Okayo, Robert O.; Andika, Darius O.; Dida, Mathews M.; K’Otuto, George O.; Gichimu, Bernard M. (Hindawi, 2020)
Pathogenesis of Aspergillus flavus on important agricultural products is a key concern on human health due to the synthesis and secretion of the hazardous secondary metabolite, aflatoxin. &is study identified and further characterized aflatoxigenic A. flavus from groundnuts sampled from sundry shops in Kenya using integrated morphological and molecular approaches. &e groundnuts were plated on potato dextrose agar for isolation and morphological observation of A. flavus based on macroscopic and microscopic features. Molecular characterization was done through amplification and comparison of the partial sequence of the ITS1-5.8S-ITS2 region. &e expression analysis of aflR, aflS, aflD, aflP, and aflQ genes in the aflatoxin biosynthesis pathways was conducted to confirm the positive identification of A. flavus. &e gene expression also aided to delineate toxigenic isolates of A. flavus from atoxigenic ones. Morphologically, 18 isolates suspected to be A. flavus were identified. Out of these, 14 isolates successfully amplified the 500 bp ITS region of A. flavus or Aspergillus oryzae, while 4 isolates were not amplified. All the remaining 14 isolates expressed at least one of the aflatoxigenic genes but only 5 had all the genes expressed. Partial sequencing revealed that isolates 5, 11, 12, 13, and 15 had 99.2%, 97.6%, 98.4%, 97.5%, and 100% homology, respectively, to the A. flavus isolate LUOHE, ITS-5.8S-ITS2, obtained from the NCBI database. &e five isolates were accurate identification of atoxigenic A. flavus. Precise identification of toxigenic strains of A. flavus will be useful in establishing control strategies of the fungus in food products.